Measuring positive and negative aspects of youth behavior: Development and validation of the Adolescent Functioning Scale. (20th August 2016) - Dittman, Cassandra K.; Burke, Kylie; Filus, Ania; Haslam, Divna; Ralph, Alan
ABSTRACT: This paper outlines the development and validation of the Adolescent Functioning Scale (AFS) in an Australian sample of parents of young people aged 11–18 years ( N = 278). The AFS, a parent self‐report measure, was designed to assess problem behavior and positive development in adolescents. Principal components analysis produced a 33‐item measure comprising four subscales: Positive Development, Oppositional Defiant Behavior, Antisocial Behavior and Emotional Difficulties. Convergent validity was established via correlations between the AFS and established measures of adolescent functioning and parenting, and discriminant validity was shown through no association between the AFS and a measure of technology use. Internal consistency for the subscales was high ( H = .82–.92 for different age groups), as was test‐retest reliability ( r = .77–.86). The study indicated that the AFS is a potentially valuable tool for assessing levels of problem behaviors and positive development in adolescents.